Applying the institutional review board data repository approach to manage ethical considerations in evaluating and studying medical education. Issue 1 (1st January 2016) - Thayer, Erin K.; Rathkey, Daniel; Miller, Marissa Fuqua; Palmer, Ryan; Mejicano, George C.; Pusic, Martin; Kalet, Adina; Gillespie, Colleen; Carney, Patricia A.
Abstract : Issue: Medical educators and educational researchers continue to improve their processes for managing medical student and program evaluation data using sound ethical principles. This is becoming even more important as curricular innovations are occurring across undergraduate and graduate medical education. Dissemination of findings from this work is critical, and peer-reviewed journals often require an institutional review board (IRB) determination. Approach: IRB data repositories, originally designed for the longitudinal study of biological specimens, can be applied to medical education research. The benefits of such an approach include obtaining expedited review for multiple related studies within a single IRB application and allowing for more flexibility when conducting complex longitudinal studies involving large datasets from multiple data sources and/or institutions. In this paper, we inform educators and educational researchers on our analysis of the use of the IRB data repository approach to manage ethical considerations as part of best practices for amassing, pooling, and sharing data for educational research, evaluation, and improvement purposes. Implications: Fostering multi-institutional studies while following sound ethical principles in the study of medical education is needed, and the IRB data repository approach has many benefits, especially for longitudinal assessment of complex multi-site data.